THE IMPORTANCE OF THE APPLICATION OF PROTECTIVE COATINGS IN INCREASING THE SERVICE LIFE OF AGRICULTURAL TECHNIQUES USED IN THE AGRICULTURAL ENVIRONMENT - Khojimatov A. A. (Bright Mind Publishing, 2025)
Machines manufactured in mechanical engineering operate under very diverse conditions. In this case, protective coatings, in addition to general factors, are subject to specific (special) effects, mostly aggressive factors. Therefore, the study of protective coatings is considered important.
Keywords: Aggressive environment, machinery, mechanism, durability, factor, coating, requirement, protection level, adhesion, storage.